Extensive Bone Lengthening for a Patient with Linear Morphea - Kenichi Mishima; Hiroshi Kitoh; Masaki Matsushita; Tadashi Nagata; Yasunari Kamiya; Naoki Ishiguro (Case Reports in Orthopedics)
Localized scleroderma, also known as morphea, is a rare condition characterized by progressive sclerosis of the skin and associated atrophy of the underlying tissues. The linear type of localized scleroderma is the most frequent form in childhood, usually affecting unilateral extremities. Fibrosclerosis of the fasciae and muscles can spread across joints and impair the range of motion of the joint. Dysplastic and/or atrophic bones of the affected lower extremity can lead to clinically significant leg length discrepancy (LLD). Limb reconstruction surgery has rarely been indicated for LLD in patients with linear morphea. We report on a case of extensive bone lengthening for appreciable LLD in a pediatric patient with linear morphea. A Japanese girl with linear morphea underwent staged simultaneous lengthening of the femur and tibia twice at seven and eleven years of age using a unilateral external fixator. A healing index exceeded 100 days/cm except for the first femoral lengthening that was complicated by regenerate fracture. At the final follow-up, LLD of 38 mm remained, but she could walk independently without a brace or a crutch. Due to soft tissue tightness and poor regenerative ability in the affected limb, cautions should be taken to prevent regenerate fracture and/or malalignment of the limb.